Path Analysis of the Effect of Safety Climate and Job Satisfaction on Safety Behavior of Seafarers Using PLS - Puspitacandri, Ardhiana; Moejiono, Moejiono (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2025)
This study aims to analyze the path of effect through which safety climate and job satisfaction influence sailors’ safety behavior. The population in this study comprises the deck crew (seafarers) from several domestic shipping companies, totaling 210 individuals. The sample was selected using simple random sampling with data collected from 141 seafarers. The data were processed using Partial Least Square (PLS) with PLS Smart Software. The results indicate a direct and significant positive relationship between safety climate and safety behavior, with a path coefficient value of 0.421. Additionally, there is an indirect effect of safety climate on safety behavior mediated by job satisfaction, with a path coefficient value of 0.177. The analysis also reveals a significant positive relationship between safety climate and job satisfaction, with a path coefficient of 0.631, and a direct significant positive relationship between job satisfaction and sailors’ safety behavior, with a path coefficient value of 0.280. The structural model analysis using PLS demonstrates that safety climate and job satisfaction influence sailors’ safety behavior, with an overall predictive power of 52.45%. This indicates that the overall predictive capability of the model is considered strong. Although the safety climate and job satisfaction influence the safety behavior of ship crews, there are also other factors such as intelligence (IQ), special skills, physical condition, personality, emotions, thinking style, perceptions, and work attitudes that can influence behavior as external factors in this study. As a practical recommendation, shipping companies are advised to improve the safety climate and job satisfaction. This can be done by providing safety facilities, regular training, policies that priorities crew safety, and effective communication between management and employees.